Preposition’s Meaning of Construction -s on The Novel “The Da Vinci Code” - Elita Sanjaya; Irpan Ali Rahman (e-LinguaTera, 2023)
The goal of the study is to prove that prepositions can parse the meanings of possessive construction -s. Besides, it is also to describe kinds of prepositions occurring in the possessive construction -s and to explain the meanings of possessive construction -s. Theories employed to support in analyzing data are Murphy (1998) talking about prepositions; Lyons (1995), Huddleston & Pullum (2002), Carter & McCarthy (2010) discussing about possessive construction -s. The research questions discussed in this study are what kinds of prepositions can the possessive construction -‘s substitute and what meanings can the possessive constructions emerge. Some people considered that the possessive construction -‘s as the meaning of possession of someone. Based on the findings found by the writer, the meaning of possessive construction -s is not only to refer to the possessive meanings, but also to meanings of preposition, i.e. at, in, on, to, of, from, by, and about. Besides, each preposition has different meanings depending on contexts of the sentences.